English Teachers’ Experiences with Constructivist Strategies: A Case Study in Indonesian Contexts - Habibah, Nor; Nor, Hidayah (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study investigates the implementation and perceived advantages of constructivist strategies in English language teaching by English teachers at SMAS PGRI 7 Banjarmasin, Madrasah Aliyah Darul Imad, and MAN 2 Banjarmasin. Employing a qualitative case study approach, data were collected through observation, interviews, and documentation from three English teachers across the three schools. Data analysis followed the methods of Miles and Huberman (2014), including data reduction, data display, and conclusion drawing. The findings reveal that teachers integrated various constructivist learning models, such as problem-based learning, task-based learning, and role-playing. Six key advantages for teachers emerged from implementing these strategies: (1) fostering independent problem-solving among students, (2) creating a more conducive learning environment, (3) enhancing student activity and creativity, (4) promoting critical thinking, (5) facilitating free expression of student ideas, and (6) making learning more meaningful. In conclusion, constructivist teaching strategies are effective in elevating the quality of English language instruction. While this student-centred approach emphasizes active classroom participation, it also provides a framework for English teachers. The study highlights the strategy’s utility in encouraging passive students to engage more actively, underscoring the importance of teachers providing engaging classes for all students.